Development of iOS/Android apps for vector calculus with 3D visualization - Tay, Jia Xin (Nanyang Technological University, 2021)
The study of partial differential equations and differential geometry relies heavily on vector calculus. It is widely used in engineering and physics, particularly in the fields of electromagnetic fields, gravitational fields, and fluid flow. To put it another way, it is primarily linked to three-dimensional (3D) space. The ability to visualize in a 3D environment is an essential skill in the field of engineering. As a result, the project's goal is to build a mobile application for 3D vector visualization to help them with their work that requires 3D vector. This paper examines the project's use of MATLAB and other related languages. It also explores possibility of conversion an EXE file to APK file that runs on Android Device.